Investigation of Opinions of Seventh Grade Students about Socio-Scientific Issues by means of Science Teaching Based on Common Knowledge Construction Model - Hasan Bakırcı; Hüseyin Artun; Serkan Şahin; Müge Sağdıç (Anı Publishing, 2018)
The aim of this study is to investigate the opinions of seventh-grade students on socio-scientific issues through science teaching based on a common knowledge construction model. The study was carried out with 25 grade seven students attending a secondary school in the spring term of the 2016-2017 academic year. Within case study research methodology, one of qualitative research methods, was applied. In the study, the Socio-Scientific Issues Evaluation Form and semi-structured interview questions were used for data collection. In analyzing the data content analysis were used. The findings indicated that the students found socio-scientific issues were complex, open-ended and mostly debatable issues which did not any have clear-cut answer. The CKCM lessons sequence was found to be influential on the development of the 7th grade students' decision-making skills regarding socio-scientific issues, problem-solving skills in daily lives and the development of science literacy. To clarify the effect of the CKCM on socio-scientific issues, future studies should be conducted with a larger sample from different grades.